Outcome of Laparoscopic Intra-Abdominal Ventral Hernia Repair with Tissue Separating Mesh - Junaid Khalid, M. Usama Shabbir, Muhammad Asadullah Khawaja, Mohammad Akmal Shafiq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the outcome of laparoscopic Intra-abdominal Ventral Hernia Repair with Tissue Separating Mesh. Methodology: Patients aged 18-60 years old with documented ASA grade I or II, ventral hernias >5 cm in size (clinically assessed by palpable expansile cough impulse and as abdominal wall defect on ultrasound), and no general contraindications to laparoscopy (such as bleeding disorders, low platelet counts, or prolonged clotting times) were excluded. Patients’ permission was obtained after they were fully informed of the risks and benefits. Name, age, gender, and contact details were also recorded. After that, laparoscopic ventral hernia repair was performed. These surgeries were performed under general anaesthesia by a single surgical team led by a senior doctor with at least three years of expertise in laparoscopic surgery. The moment of incision served as the starting point. Tissue-separating mesh was inserted intraoperatively, and the operational time was recorded once again during closure. The patients were sent to the ward for further observation. Discharge documentation revealed a patient’s postoperative hospital stay. Results: Mean age of the patients was calculated as 37.03+11.32 years. The gender breakdown reveals that men as majority, with 51 (51%) compared to 49 (49%) females. The outcome of laparoscopic intra-abdominal ventral hernia repair using tissue Separating Mesh showed that the mean operation time was 116.21+8.27 minutes, and the length of hospital stay was documented as 2.4+0.38 days. Conclusion: We concluded that outcome of laparoscopic Intra-abdominal Ventral Hernia Repair with Tissue Separating Mesh with regards to duration of operation and post operative hospital stay is feasible in our population Keywords: Intra-abdominal Ventral Hernia Repair, Tissue Separating Mesh, outcome, post-operative hospital stay, duration of operation